Factors correlated with health-related quality of life among elderly outpatients with chronic obstructive pulmonary disease from selected hospitals in Malaysia - Yahya, Nor Farahain (2019)
The prevalence and mortality rate of Chronic Obstructive Pulmonary Disease (COPD) is in the increasing trend, especially among elderly people. As COPD is an incurable disease, improving patient’s Health-related Quality of Life (HRQOL) need to be the main focus area in management. However, most of the study on HRQOL was conducted among younger adult people. Thus, limited information on elderly people especially in Malaysia. Therefore, to fill the gaps, this study was conducted to determine factors correlated with HRQOL in elderly outpatients with COPD from selected hospital in Malaysia. The factors examined in this study were socio-demographic, health status, nutrition status, functional status and sleep quality. A cross-sectional study involved 140 elderly patients diagnosed with COPD was conducted at Respiratory Clinic of Institut Perubatan Respiratori and Hospital Serdang. Data on socio-demographic and health status were collected by interviewing patients and reviewing their medical records. Nutritional status involved Body Mass Index (BMI), Fat-Free Mass Index (FFMI), body fat, weight loss, dietary intake and risk of malnutrition. Other information collected included a functional status and sleep quality. HRQOL in this study was determined by COPD Assessment Test. The mean age of patients in this study was 70 ± 7 years. Majority of the patients in this study were male (97%) Malay (59%) patients who married (75%), exsmoker (72%) and attained primary education (48%). Majority of them had a moderate stage of airflow limitation (53%) and did not visit the emergency department or experience any episode of exacerbation that required hospitalization for the past one year (57%). Most of the patients in this study had a normal BMI (53%), FFMI (78%) and body fat (45%), but they were also presented with weight loss (52%). Majority of them did not consume an oral nutrition supplement (99%). For dietary intake, patients did not have adequate energy, protein, carbohydrate, fat, vitamin A, C, D and E intake as measured by individual requirements. Over half of the patients in this study were classified as at risk of malnutrition (50%) and had poor sleep quality (65%). Apart from that, most of them had normal handgrip strength (56%) and only had a difficulty to breathe when hurrying on the level or walking up a slight (43%). The mean score of HRQOL in this study was 21 ± 6.85 and domain of functional status scored the highest. Factors such as BMI (r=-0.228, p=0.018), body fat (r=-0.191, p=0.048), risk of malnutrition (r=-0.266, p=0.005) and sleep quality (r=0.496, p=0.001) were found to be correlated with HRQOL. For breathlessness during daily activities, grade of Modified Medical Research Council showed a significant difference for HRQOL (F=15.75, p=0.001). Both, smoking history (F=2.244, p=0.022) and history of hospitalisation or visit to the emergency department due to COPD (F=0.045, p=0.030) had a mean difference in HRQOL. For multiple linear regression, four factors were found to be significantly contributed towards HRQOL, which were smoking (Beta=0.178, t=2.571, p=0.012), body fat (Beta=- 0.148, t=-2.153, p=0.034), breathlessness on daily activities (Beta=0.488, t=6.793, p=0.000) and sleep quality (Beta=0.323, t=4.462, p=0.000). These four factors can explain 51.7% (R Square) of the variation of HRQOL. In conclusion, limitations of daily activities due to breathlessness, poor sleep quality, smoking and lower body fat were significantly contributed towards poor HRQOL among elderly outpatients with COPD from Institut Perubatan Respiratori and Hospital Serdang.